The effect of maize plants as a repellent for Bemisia tabaci (Gennadius) on chili plants: Pengaruh tanaman jagung sebagai penolak Bemisia tabaci (Gennadius) pada tanaman cabai - Witjaksono, Witjaksono; Soffan, Alan; Akbar, Muhammad Aulia (Jurnal Entomologi Indonesia, 2024)
Bemisia tabaci (Gennadius) is crital pest of chili plants. Besides using chemical insecticides to control B. tabaci, the actions that can be taken for B. tabaci management include applying repellent compounds. This research aims to study the potential of various commercial corn varieties in producing repellent compounds for B. tabaci. The method used in this research involved testing the response of B. tabaci using a Y tube olfactometer and GCMS analysis on varieties P-21, Bisi-18, NK-212, and Pertiwi 3 on a laboratory scale. Volatile compounds were collected from corn plants aged 3–10 weeks after planting (WAP). The results showed that Bisi-18, P-21, NK-212, and Pertiwi 3 maize exhibited repellency against B. tabaci. The highest repellency for all corn varieties was observed at 10 WAP. The P-21 variety exhibited 80% repellency, followed by Pertiwi 3 and Bisi-18 with 78% repellency, while NK-212 showed the weakest repellencyat 60%. Results from volatile compounds identification of each maize varieties demonstrated revealed several compounds with repellent properties against B. tabaci, including 9-otadecenoic acid (Z)-, 9-octadecenamide, (Z)-, delta-guaiene, alpha-guaiene, beta caryophyllene, and patchouli alcohol. Using maize plants to manage B. tabaci has the potential to be an environmentally friendly management technique. Further research is needed on B. tabaci management technique to achieve a more effective and efficient combination.